Faktor-Faktor yang Berhubungan dengan Kecelakaan Kerja di PT. Pijar Sukma Jepara - Lana Labibatul Ulya; Anik Setyo Wahyuningsih (Jurnal Kesehatan Masyarakat, 2023)
PT. Pijar Sukma is a furniture manufacturer company specializing in handmade finishing with a classic French concept that is located in Jepara. Based on the records, there were many cases of work accidents that occurred in the company. In 2017, there were 13 cases of work accidents. In 2018 there was an increase in the number of work accidents to 25 cases. In 2019 the number of work accidents decreased to 10 cases. In 2020 it decreased again to 6 cases. In 2021 there was an increase again to 9 cases and in 2022 it decreased to 7 cases.This type of research was an analytical observational study with a quantitative approach that used a cross sectional study design. The population in this study were production workers at PT. Pijar Sukma. The research sample consisted of 81 samples selected using simple random sampling technique. The instrument used is a questionnaire. then the data were analyzed using chi square.The results showed that the variables associated with work accidents were years of service (p=0,023), use of PPE (p=0,001),  level of education (p=0,029), and knowledge of OSH (p=0,044).Thus, it is necessary to increase supervision and socialization about OSH and increase knowledge of OSH through training and safety talk so that workers can work safely.